The association between children’s exposure to pesticides and asthma, wheezing, and lower respiratory tract infections. A systematic review and meta-analysis - Keleb, Awoke; Daba, Chala; Asmare, Lakew; Bayou, Fekade Demeke; Arefaynie, Mastewal; Mohammed, Anissa; Tareke, Abiyu Abadi; Kebede, Natnael; Tsega, Yawkal; Endawkie, Abel; Kebede, Shimels Derso; Abera, Kaleab Mesfin; et al. (Frontiers in Public Health, 2024)
Background: Exposure to pesticides is a global public health problem especially for children. Its association with chronic respiratory disease among children has attracted considerable attention but existing evidence remains inconclusive that cannot be certain. Therefore, the aim of this systematic review and meta-analysis is to determine the global pooled effect size of association with pesticide exposure and asthma, wheeze and respiratory tract infections among children.Methods: A comprehensive search was conducted for relevant literature from electronic databases, including PubMed, Google Scholar, Hinari, Semantic Scholar, and Science Direct.Studies that provided effect size on the association between pesticide exposure and childhood asthma, wheeze and respiratory tract infections in children were included. The articles were screened, data was extracted and the quality of each study was assessed with four independent reviewers. Random-effects model for significant heterogeneity and fixed effect model for homogeneous studies were conducted to estimate pooled effect sizes with 95% confidence intervals using Comprehensive Meta-Analysis version 3.3.070 and MetaXL version 2. Funnel plot and Higgs I 2 statistics were used to determine the heterogeneity of the included studies. Subgroup analyses were computed based on the types of pesticide exposure, study design, sample size category, and outcome assessment technique.Result: A total of 38 articles with 118,303 children less than 18 years of age were included in this meta-analysis. Pesticide exposure among children increased the risk of asthma by 22%; (OR=1.24, 95%CI: 1.14-1.35) with extreme heterogeneity (I 2 =81%, P < 0.001). Exposure to pesticide increased the odds of developing wheeze among children by 34% (OR=1.34, 95%CI: 1.14-1.57), with high heterogeneity (I 2 =79%, P < 0.001,) and also increased the risk of developing lower respiratory tract infection by 79%(OR=1.79, 95%CI: 1.45-2.21) with non-significant low heterogeneity (I 2 = 30%, P-value = 0.18) Conclusion: This meta-analysis provided valuable evidence supporting the association between childhood asthma, wheeze and lower respiratory tract infection with pesticide exposure. The findings would contribute to a better understanding of the estimate of effect of pesticide exposure on respiratory health in children and inform evidence-based preventive strategies and public health interventions